Mechanical rotational chair-assisted multiple canalith repositioning procedures for benign paroxysmal positional vertigo: enhanced vertigo relief, comparable adverse effects, and decreased incidence of residual dizziness - Zhang, Hao; Zhu, Meijia (Frontiers in Neurology, 2023)
Objectives This retrospective study aimed to assess the effectiveness and adverse effects of mechanical rotational chair-assisted multiple canalith repositioning procedures (CRPs) to treat benign paroxysmal positional vertigo (BPPV). Materials and methods A retrospective analysis of 1,273 BPPV patients was conducted, with 241 patients included in the final study. The participants diagnosed with BPPV, unresolved by a single previous CRP, were categorized into either the single or multiple CRP groups. In both groups, on days 1, 4, and 7 after the initial treatment, the participants were re-evaluated after a single CRP; if positional vertigo was resolved, the treatment was regarded as successful. The remission rate, adverse effects (such as canal switch (CS), falls, and vomiting), residual dizziness (RD) rate, and RD duration were compared between the two groups. Results The resolution rates for the single and multiple CRP groups were significantly different on days 1 and 4 (55.7% vs. 85.1%, 75.5% vs. 91.9%; P < 0.05) but not on day 7 (93.3% vs. 94.8%; P > 0.05). There were no significant differences between the single and multiple CRP groups in terms of CS and falls (3.8% vs. 5.2%, 10.3% vs. 8.9%; P > 0.05). However, there was a significant difference in the incidence of vomiting (6.6% vs. 14.8%; P < 0.05). RD such as head heaviness, imbalance, and non-specific dizziness is more common in the single CRP group than in the multiple CRP group (34.9% vs. 20.7%, 42.5% vs. 26.7%, 47.2% vs. 32.6%; P < 0.05). The incidence and duration of RD were notably diminished in the group undergoing multiple CRPs compared to the single CRP group, with incidence rates of 41.5% and 57.5%, respectively (P < 0.05). Conclusion For patients with BPPV, multiple CRPs offer greater benefits than a single CRP.